Struktur Mikroanatomi Testis Tikus Putih (Rattus norvegicus) Setelah Pemberian Teh Kombucha Konsentrasi 75% Waktu Fermentasi 6, 9 Dan 12 Hari - Isdadiyanto, Sri; Tana, Silvana (Bioma : Berkala Ilmiah Biologi, 2019)
The objective of this study was to analyze the testicular microanatomy structure of Rattus norvegicus after treatment by 75% kombucha tea with variation of fermentation time. Sixteen male of rats, 2 months of age were used as experimental animals treated with kombucha tea that had been fermented for 6, 9 and 12 days at the temperature of 25oC per oral. This research was using completely randomized design with 4 treatment (for 4 weeks) and 4 replications, namely: P0 = control, without of kombucha tea, P1 = water + 1,8 ml kombucha tea that had been fermented for 6 days in the morning and afternoon, P2 = water + 1,8 ml kombucha tea that had been fermented for 9 days in morning and afternoon, P3 = water + 1,8 ml kombucha tea that had been fermented for 12 days in morning and afternoon. The variables measured were seminiferous tubule diameter and Leydig cell counts. Data were analyzed with ANOVA followed by Duncan test at 95% confidence level were performed using SPSS version 16,0. The results showed that kombucha tea decreased the diameter of the seminiferous tubule, showing the potention of spermatogenesis disturbance, but did not affect Leydig cell counts of Rattus norvegicus